P110 Self-taken samples for chlamydia and gonorrhoea in HIV outpatients are acceptable and perceived as reliable and comfortable by patients. (18th May 2015) - Croucher, Adam; Buckingham, Tracey; Richardson, Daniel
Abstract : Introduction: Self-taken samples increase testing for Chlamydia and Gonorrhoea in high-risk asymptomatic populations including HIV-outpatients. Women are offered self-taken vaginal samples; heterosexual men first-pass urine and MSM self-taken rectal and throat samples and first-pass urine. The acceptability of this method of testing is not well understood. Methods: An anonymous paper survey was offered to all patients attending outpatient-HIV clinic June–July 2014. Data collected: age, gender, ethnicity, sexual-orientation; perceptions of self-taken samples; whether they tested that day, and why. Results: 121 surveys were returned. Median age = 45(20–69)years; 86% male; 68% white British; 73% homosexual. 61/121(50%) rated STI screening as 'very important', 48/121(39%) as 'worthwhile': 117/121(96%) rated offering self-taken samples in routine HIV clinic as appropriate. 86/121(71%) found the instructions 'easy' to follow and 4/121(3%) 'difficult'. 78/121(64%) said that they thought that self-taken samples are as reliable compared to clinician-taken and 10/121(8%) thought they were more reliable. 60/121(50%) said self-taken samples were as comfortable as clinician-taken; 30/121(25%) said more comfortable. 33/121(27%) responders did self-sampling that day; 78/121(64%) did not. Participants' reasons for accepting self-taken samples included: 'It's easier/quicker than going to a GUM clinic' (37%); 'I prefer doing the swabs myself' (25%). Reasons for not self-sampling included: 'I haven't had any sex since my last sexual health screen' (26%); 'I was not offered a STI screen today' (20%); 'I prefer to go to a GUM clinic' (16%). Conclusions: The self-swab STI screens are acceptable to patients attending HIV outpatients', and are perceived as being as reliable and as comfortable as clinician-taken samples.